A thorough investigation of the Bi2O3-PbCl2-TeO2 system: Glass forming region, thermal, physical, optical, structural, mechanical and radiation shielding properties - Ersundu, Ali Ercin; Sayyed, M., I; Kibrisli, Orhan; Akilli, Volkan; Ersundu, Miray Celikbilek (ELSEVIER SCIENCE SA, 2021)
In the present work, a series of glasses in the Bi2O3-PbCl2-TeO2 system are synthesized by conventional melt quenching technique. Glass forming region of the specially designed glass system is determined. Thermal properties of glasses - glass transition (T-g) and crystallization (T-c/T-p) temperatures and glass stability against crystallization (Delta T) - are determined. Density and refractive index values are measured to interpret various physical properties of glasses. Optical and structural properties are studied through visible transmittance and Fourier transform infrared spectroscopy analysis. Mechanical properties are investigated by Vickers hardness measurements. The radiation shielding competence of glasses is evaluated in the energy range from 0.161 MeV to 2.51 MeV using Phy-X/PSD simulation program. The mass attenuation coefficient (MAC), linear attenuation coefficient (LAC), effective atomic number (Z(eff)), half value layer (HVL), tenth value layer (TVL) and mean free path (MFP) are calculated. Glasses in the Bi2O3-PbCl2-TeO2 system possess superior shielding effectiveness than other commercially available radiation shielding glasses owing to higher MAC and lower HVL and MFP values. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Tellurite glasses; Density; Radiation shielding; Tenth value layer; Phy-X/PSD; FEATURES; BI2O3; OXIDE; TEO2; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering